2020
DOI: 10.7150/jca.50477
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzyme USP1 modulates ERα and modulates breast cancer progression

Abstract: Breast cancer is one of the most common malignancies worldwide, while the luminal types (ERα positive) accounts for two third of all breast cancer cases. Although ERα positive breast cancer could be effective controlled by endocrine therapy, most of the patients will develop endocrine resistance, which becomes a headache clinical issue for breast cancer field. Endocrine resistance could be caused by multiple pathway disorders, the dys-regulation of ERα signaling might be a critical factor, which makes it urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…As a key component of UPS, DUBs participate in the regulation of cell cycle, apoptosis, proliferation and other behaviors [ 25 ]. Importantly, the dysregulation of DUBs leads to the progression of numerous human malignancies, including digestive cancers [ 26 ], breast cancer [ 27 29 ], OSCC [ 30 ] and HNSCC [ 31 ]. In this study, we analyzed public databases online and identified several significantly upregulated DUBs including JOSD1.…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of UPS, DUBs participate in the regulation of cell cycle, apoptosis, proliferation and other behaviors [ 25 ]. Importantly, the dysregulation of DUBs leads to the progression of numerous human malignancies, including digestive cancers [ 26 ], breast cancer [ 27 29 ], OSCC [ 30 ] and HNSCC [ 31 ]. In this study, we analyzed public databases online and identified several significantly upregulated DUBs including JOSD1.…”
Section: Discussionmentioning
confidence: 99%
“…Several DUBs, such as USP1, USP7, and USP22, have been shown to play regulatory roles in ERα signaling. They deubiquitinate ERα and activate its relative signaling pathway to promote ERα + breast cancer development [ 76 , 77 , 78 ]. USP11 positively regulates ERα transcriptional activity in breast cancer cells in an E2-dependent manner [ 79 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…USP1 is also an essential deubiquitinase in ERα signaling, which enhances ERα stability through cleaving its Lys48-linked ubiquitin chains. According to TCGA and KMPLOT databases, high expression of USP1 is relevant to poor prognosis in ERα + breast cancer patients [ 93 ].…”
Section: Dubs In Chemoresistance and Chemosensitivity Of Breast Cancermentioning
confidence: 99%